2021
DOI: 10.3390/pathogens10050628
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Coronaviruses: Observations from Veterinary Experience

Abstract: The virus responsible for the pandemic that has affected 152 countries worldwide is a new strain of coronavirus (CoV), which belongs to a family of viruses widespread in many animal species, including birds, and mammals including humans. Indeed, CoVs are known in veterinary medicine affecting several species, and causing respiratory and/or enteric, systemic diseases and reproductive disease in poultry. Animal diseases caused by CoV may be considered from the following different perspectives: livestock and poul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Although mathematical models have been used to estimate the epidemiological consequences of swine disease introduction, existing models do not often account for within-barn dissemination pathways, such as the airborne transmission (Pozzi et al, 2021;Sørensen et al, 2020;Ssematimba et al, 2022;Tuominen et al, 2022Tuominen et al, , 2023. The speed in which pathogens propagate within swine farms depends on multiple factors, including within-herd disease prevalence, pathogen's virulence (Machado et al, 2022;Malladi et al, 2022), and population factors such as farm size, production types, barn sizes, and barn ventilation systems (Busch et al, 2021;Machado et al, 2022;Mighell & Ward, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although mathematical models have been used to estimate the epidemiological consequences of swine disease introduction, existing models do not often account for within-barn dissemination pathways, such as the airborne transmission (Pozzi et al, 2021;Sørensen et al, 2020;Ssematimba et al, 2022;Tuominen et al, 2022Tuominen et al, , 2023. The speed in which pathogens propagate within swine farms depends on multiple factors, including within-herd disease prevalence, pathogen's virulence (Machado et al, 2022;Malladi et al, 2022), and population factors such as farm size, production types, barn sizes, and barn ventilation systems (Busch et al, 2021;Machado et al, 2022;Mighell & Ward, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies focusing on this topic from an animal perspective were included. The first paper by Pozzi et al [ 1 ] showed that the experiences amassed during the long-lasting war against Coronaviruses in animal medicine provide some useful information that may be applicable to COVID-19, such as the control of air inlets in healthcare facilities. Another paper by Soltane et al [ 2 ] investigated the potential application of structural analogues prepared from natural maslinic and oleanolic acids against the SARS-CoV-2 main protease as a tool for developing new therapeutical approaches, with interesting results.…”
mentioning
confidence: 99%